A study of the non-use of the veto power within the United Nations security council - Karodia, Nadia (My University, 2018)
This paper analyses the concept of the non-use of the veto in the United Nations Security Council (UNSC). The crisis in Syria is still a prominent tragedy that we face today, and we have seen China and Russia use their vetoes to block action in Syria. This paper uses Syria as a case study and narrows the scope by analysing only those issues that relate to crimes against humanity. This paper unpacks the emerging campaigns relating to veto restraint. The success of the veto restraint campaigns, and an analysis of how the permanent members of the UNSC have responded to these campaigns, are made. The power politics and norms of humanitarian intervention are assessed through the theoretical frameworks of Realism and Constructivism, in order to understand whether these factors have influenced the non-use of the veto. The findings indicate that both power politics and norms of humanitarian intervention have influenced the non-use of the veto, and any other resolutions that have been adopted (which are non-use examples) cannot be explained by the veto restraint campaigns
A thesis submitted to the Faculty of Humanities in fulfilment of the requirement for the degree Master of Arts in International Relations, University of the Witwatersrand, Johannesburg, 2018
Keywords: United Nations--Armed Forces; Armed Forces; Welfare state